New perspectives of the treatment of urogenital atrophy in women: intravaginal DHEA therapy - Gałczyński, Krzysztof; Poleszak, Ewa; Kasperek, Regina; Romanek-Piva, Katarzyna; Kulik-Rechberger, Beata; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2013)
According to novel theory menopausal symptoms are not only connected with estrogen deficiency due to diminished ovarian estrogen secretion, but are also associated with the gradual, progressive decline in the level of dehydroepiandrosterone (DHEA) secreted by the adrenal glands. Over 50% of postmenopausal women report symptoms associated with urogenital atrophy, ie: irritation, recurrent infections, dryness, dyspareunia. Systemic hormonal therapy with estrogens or in combination with progestins is an effective treatment of these symptoms, however, it is associated with some adverse effects. In addition, it is worthwhile to think about local therapy in case of women who have only symptoms associated with urogenital atrophy. Promising are results of the studies of DHEA intravaginal therapy, in which it was assumed that physiological doses of DHEA contribute to an increase in androgens and estrogens synthesized locally in tissues by intracrine mechanisms with low systemic effects. Previous studies have shown that intravaginal DHEA application reduce the symptoms of vaginal atrophy, regress low-grade cervical dysplasia and increase libido.